The development of picture modules in health education for the pre-school children - Intal, Josefina F. (1986)
This study developed picture modules for pre-school education which took into consideration individual differences and age level of the learners. It underlines the importance of health education in the pre-school health curricula.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Typescript.
Keywords: Health education (Preshool) -- Audio-visual materials